Linguistic Socialization and Identity in Ethnic Hungarian Deaf Families in Romania - Belényi, Emese; Flóra, Gábor (Central European Journal of Educational Research, 2020)
Ethnic minority Deaf people form a social group whose members often share complex and multiple cultural backgrounds. This research explores linguistic socialization and identity development in ethnic Hungarian Deaf families living in a multi-cultural region of Romania, examining the identity related aspects of the family formation and the transmission of identity to children in ethnically homogenous (Hungarian) or heterogeneous (Hungarian-Romanian) families founded by Deaf spouses. Methodologically the research is based on survey among members of the ethnic Hungarian Deaf community in Bihor County and their ethnic Romanian spouses, career interviews with Hungarian Deaf Special School graduates and family case studies of two or three generation Deaf families. The research results reveal that the ethnic homogeneity of Deaf family partners is a key factor in handing down to children the Hungarian ethnic-national identity and the Hungarian sign language / oral language knowledge. The research findings also highlight the fact that within family interactions involving three generations where Deaf and hearing, ethnic minority and ethnic majority family members are present, specific, multifaceted communication models may prevail, and pathways and modes of identity transmission with particular characteristics may occur.